Implementasi Kurikulum 2013 pada Pendidikan Vokasi di Indonesia - Rido Putra; Iffarial Nanda; Rifdarmon Rifdarmon; Suci Suci; Nuzul Hidayat (Dinasti Research, 2023)
One of the problems with vocational education is the unpreparedness of graduates because they do not yet have competence in the world of work. Apart from that, local graduates are not yet able to compete with foreign graduates. The efforts made by the government are by innovating or developing the KTSP curriculum into the 2013 Curriculum. The 2013 Curriculum requires students to be more active and creative in the learning process. The 2013 curriculum that was developed is very appropriate to use because the indicators in the 2013 curriculum can familiarize students when they graduate. However, the implementation of the 2013 curriculum still experiences obstacles such as a lack of understanding by teaching staff regarding the 2013 curriculum which makes the learning process hampered